Character education and building the nation’s character through military conscription - Wakhudin (Universitas Jambi, Indonesia, 2025)
This research aimed to describe the role of military service in building the national character Indonesia needs today. This research employed a qualitative-descriptive approach, utilizing a discourse analysis method. The discourse analysis process was carried out by determining the text or discourse to be analyzed. In this case, the selected texts are